Undergraduate Students' Perceptions of Using AI: Is Quillbot Helping Students' Writing? - Fajriatun Nurjanah; Tien Rafida (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2024)
QuillBot is an application that uses artificial intelligence algorithms to help users produce coherent writing. It helps undergraduate students find errors in writing, such as punctuation, grammar, and others, because QuillBot offers features that facilitate students' writing effectively, such as language enhancement, grammar correction, and paraphrasing. The objective of this study is to investigate the ways in which QuillBot enhances confidence in writing and facilitates the assistance of writing abilities through a descriptive qualitative study. Data were collected through questionnaires and semi-structured interviews that were analyzed by using thematic analysis. The participants of this research were 31 students whose writing level is already at the advanced writing level. The results showed that undergraduate students responded positively, such as increasing their confidence when writing so they did not hesitate to write because QuillBot provides suggestions for improving writing identifying and correcting less clear sentences. Talking about its technical support, QuillBot is also easy to use without a long process and does not waste time. QuillBot offers valuable and helpful features for students because its features make it easy for them to improve their writing.